2015
DOI: 10.1017/s0007114514003766
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between fermented food intake and mortality risk in the European Prospective Investigation into Cancer and Nutrition-Netherlands cohort

Abstract: The objective of the present study was to investigate the relationship between total and subtypes of bacterial fermented food intake (dairy products, cheese, vegetables and meat) and mortality due to all causes, total cancer and CVD. From the European Prospective Investigation into Cancer and Nutrition-Netherlands cohort, 34 409 Dutch men and women, aged 20-70 years who were free from CVD or cancer at baseline, were included. Baseline intakes of total and subtypes of fermented foods were measured with a valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 29 publications
(49 reference statements)
4
48
0
Order By: Relevance
“…There is mixed evidence from prospective studies concerning a role of dairy food consumption in mortality risk (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Consistent with our results, in the Whitehall II Study (21), higher consumption of dairy products was associated with reduced all-cause mortality risk in comparison with the lowest intake.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…There is mixed evidence from prospective studies concerning a role of dairy food consumption in mortality risk (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Consistent with our results, in the Whitehall II Study (21), higher consumption of dairy products was associated with reduced all-cause mortality risk in comparison with the lowest intake.…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings for total dairy products and mortality risk have been reported among men and women in Switzerland (22). Previous findings in the Whitehall II Study (21), the Rotterdam Study (23), the Hoorn Study (24), and the European Prospective Investigation into Cancer and Nutrition-Netherlands (EPIC-NL) cohort study (25) did not support a significant inverse association between yogurt consumption and CVD mortality risk. We observed that yogurt consumption was associated with lower risk of all-cause and CVD mortality.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations